Taxonomic revision of Peperomia (Piperaceae) from Uruguay - Mai, Patricia; Rossado, Andrés; Bonifacino, José Mauricio; Waechter, Jorge Luiz (Phytotaxa, 2016)
The genus Peperomia is represented by eight species in Uruguay: P. catharinae, P. comarapana, P. hispidula, P. increscens, P. pereskiifolia, P. psilostachya, P. tetraphylla and P. trineuroides. Peperomia psilostachya is reported for the first time for the flora of Uruguay, from material collected in moist hillside and riverside forests from the northeast and east of the country. Three new synonyms are proposed: P. arechavaletae var. arechavaletae as synonym of P. trineuroides, P. arechavaletae var. minor of P. tetraphylla and P. trapezoidalis of P. psilostachya. Lectotypes for P. arechavaletae, P. arechavaletae var. minor and P. tacuariana, and a neotype for P. herteri are designated. The taxonomic treatment includes synonymies used in Uruguay, morphological descriptions, distribution and habitat data, phenology, conservation assesment, observations, and material examined for each species treated. A species identification key, plant illustrations and distribution maps in Uruguay are provided.